Income inequality and population health: a political-economic research agenda. Issue 8 (8th June 2022) - Dunn, James R; Park, Gum-Ryeong; Brydon, Robbie; Wolfson, Michael; Veall, Michael; Rolheiser, Lyndsey; Siddiqi, Arjumand; Ross, Nancy A
Abstract : There is more than 30 years of research on relationships between income inequality and population health. In this article, we propose a research agenda with five recommendations for future research to refine existing knowledge and examine new questions. First, we recommend that future research prioritise analyses with broader time horizons, exploring multiple temporal aspects of the relationship. Second, we recommend expanding research on the effect of public expenditures on the inequality–health relationship. Third, we introduce a new area of inquiry focused on interactions between social mobility, income inequality and population health. Fourth, we argue the need to examine new perspectives on 21st century capitalism, specifically the population health impacts of inequality in income from capital (especially housing), in contrast to inequality in income from labour. Finally, we propose that this research broaden beyond all-cause mortality, to cause-specific mortality, avoidable mortality and subcategories thereof. We believe that such a research agenda is important for policy to respond to the changes following the COVID-19 pandemic.